1990
DOI: 10.1101/gad.4.8.1277
|View full text |Cite
|
Sign up to set email alerts
|

In vivo footprint and methylation analysis by PCR-aided genomic sequencing: comparison of active and inactive X chromosomal DNA at the CpG island and promoter of human PGK-1.

Abstract: The promoter region of the X-linked human phosphoglycerate kinase-I [PGK-I) gene is a CpG island, similar to those often found near autosomal genes. We used ligation-mediated polymerase chain reaction (PCR) for a genomie sequencing study in which 450 bp of the human PGK-1 promoter region was analyzed for the presence of in vivo protein footprints and cytosine methylation at all CpG sites. A technique was devised to selectively visualize the DNA of the inactive X chromosome (Xi), even in the presence of the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(193 citation statements)
references
References 63 publications
(51 reference statements)
10
182
1
Order By: Relevance
“…4A and 5); therefore, CTCF binding maintains the hypomethylated state of the ICR in somatic cells, i.e., binding to the maternal ICR is required for excluding methyltransferases from the region. Similarly, the hypomethylated state of CpG islands, which are often coincident with promoters, might result from the exclusion of methyltransferases by bound transcription factors (5,22,27). The paternal ICR became methylated in the male germ line, and this methylation persisted into somatic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A and 5); therefore, CTCF binding maintains the hypomethylated state of the ICR in somatic cells, i.e., binding to the maternal ICR is required for excluding methyltransferases from the region. Similarly, the hypomethylated state of CpG islands, which are often coincident with promoters, might result from the exclusion of methyltransferases by bound transcription factors (5,22,27). The paternal ICR became methylated in the male germ line, and this methylation persisted into somatic development.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that establishment of differential methylation is a function autonomous to the ICR (15), but the germ line-specific processes that establish this differential ICR methylation are undefined. Based on the paradigm that transcription factor binding can inhibit DNA methylation, possibly by physically blocking access of DNA methyltransferases (5,22,27), it is conceivable that differential protein binding at these sites during germ cell development may play a role in differential acquisition of DNA methylation. This could involve CTCF or another protein with an affinity for the site.…”
mentioning
confidence: 99%
“…UV Irradiation and Dimethylsulfate in Vivo Genomic Footprinting-In vivo methylation of cells with dimethylsulfate and DNA preparation were as described previously (24). In vivo UV irradiation footprinting was done essentially as described by Pfeifer and Tornaletti (25).…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that the CpG islands spanning the housekeeping type genes are protected from methylation through either (1) the process of active transcription, including the possible steric hindrance of transcription factor or DNA polymerase binding, (2) active demethylation via RNA transcripts from CpG islands possibly in combination with 5MeC-glycosylase (Jost et al, 1997), (3) replicating timing or (4) local chromatin structure that may inhibit access to the DNA methyltransferase (Kass et al, 1997). The importance of gene activity, however as the mode of protection is exemplified by the fact that the CpG islands on the inactive X chromosome are silenced prior to methylation (Pfeifer et al, 1990). Therefore, CpG islands are not intrinsically 'unmethylatable' in the early embryo but active transcription appears to be a major protective factor.…”
Section: Methylation Changes In Cancermentioning
confidence: 99%